Cord blood fatty acid binding protein 4 and lipids in infants born small- or large-for-gestational-age - Liu, Xin; Zheng, Tao; Tao, Min-Yi; Huang, Rong; Zhang, Guang-Hui; Yang, Meng-Nan; Xu, Ya-Jie; Wang, Wen-Juan; He, Hua; Fang, Fang; Dong, Yu; Fan, Jian-Gao; et al. (Frontiers in Pediatrics, 2023)
Aim: Adverse (poor or excessive) fetal growth “programs” an elevated risk of type 2 diabetes. Fatty acid binding protein 4 (FABP4) has been implicated in regulating insulin sensitivity and lipid metabolism relevant to fetal growth. We sought to determine whether FABP4 is associated with poor or excessive fetal growth and fetal lipids. Methods: In a nested case-control study in the Shanghai Birth Cohort including 60 trios of small-for-gestational-age (SGA, an indicator of poor fetal growth), large-for-gestational-age (LGA, an indicator of excessive fetal growth) and optimal-for-gestational-age (OGA, control) infants, we measured cord blood concentrations of FABP4 and lipids [high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterols, triglycerides (TG)]. Results: Adjusting for maternal and neonatal characteristics, higher cord blood FABP4 concentrations were associated with a lower odds of SGA [OR=0.29 (0.11-0.77) per log unit increment in FABP4, P=0.01], but were not associated with LGA (P=0.46). Cord blood FABP4 was positively correlated with both LDL (r=0.29, P=0.025) and HDL (r=0.33, P=0.01) in LGA infants only. Conclusion: FABP4 was inversely associated with the risk of SGA. The study is the first to demonstrate LGA-specific positive correlations of cord blood FABP4 with HDL and LDL cholesterols, suggesting a role of FABP4 in fetal lipid metabolism in subjects with excessive fetal growth.